2019
DOI: 10.1177/0300060519873473
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety can cause convulsion and severe hypotension immediately after spinal anaesthesia for caesarean delivery: a case report

Abstract: Preoperative anxiety in patients under spinal anaesthesia may cause serious complications. We report a case of combined transient convulsion and severe hypotension immediately after spinal anaesthesia for caesarean delivery in a patient who presented with severe preoperative anxiety. Our patient’s consciousness and blood pressure recovered normally without any sequelae. However, preoperative anxiety can induce such complications, particularly in patients under regional anaesthesia. Therefore, early detection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…They reported that one patient developed generalized convulsions which were attributable to pre-operative anxiety. 20 Pre-operative anxiety is a very common phenomenon and has very distressing effects on patients. It can potentially lead to various intra-operative and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that one patient developed generalized convulsions which were attributable to pre-operative anxiety. 20 Pre-operative anxiety is a very common phenomenon and has very distressing effects on patients. It can potentially lead to various intra-operative and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, studies have reported serious complications, such as convulsion and severe a hypotension, resulting from preoperative anxiety during the period of induction of regional anesthesia and surgical preparation for cesarean delivery. 30 The preoperative administration of midazolam before spinal anesthesia in patients undergoing cesarean delivery decreased anxiety without the induction of adverse neonatal effects. 31,32 However, in this study, the maternal and neonatal outcomes during the puerperal period in patients in the spinal anesthesia group did not differ according to application of intraoperative sedation.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%